Rozwiąż równania. Ułamki zwykłe zastępuje znakiem / a mnożenie *
a. 2x + 5 = 14,8 + ( x - 3 )
b. 0.25x - ( 4 + 0.5x ) = -2
c. 2 ( 3 - x ) - 4 ( x - 5 ) = 2x + 2
d. 1/3 * (-6x + 9) - 4 = -5 (x+1)
e. 0.2 * (10-5x) = 3 + 2 (x-1)
f. 37 = (20-4x) * 0.5 - 7x

Dam naaj.; ]
Prosze o pomoc!.;d

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-30T16:12:03+02:00
2x + 5 = 14,8 + ( x - 3 )
2x+5=14,8+x-3
2x-x=14,8-3-5
x=6,8

0.25x - ( 4 + 0.5x ) = -2
0.25x-4-0.5x=-2
0.25x-0.5x=-2+4
-0.25x=2
x=-8


2 ( 3 - x ) - 4 ( x - 5 ) = 2x + 2
6-2x-4x+20=2x+2
-2x-4x-2x=2-6-20
-8x=-24
x=3

1/3 * (-6x + 9) - 4 = -5 (x+1)
-2x+3-4=-5x-5
-2x+5x=-5-3+4
3x=-4
x=-4/3

0.2 * (10-5x) = 3 + 2 (x-1)
2-x=3+2x-2
-x-2x=3-2-2
-3x=-1
x=1/3

37 = (20-4x) * 0.5 - 7x
37=10-2x-7x
2x+7x=10-37
9x=-27
x=-3
2010-03-30T16:30:58+02:00
A) 2x + 5 = 14,8 + ( x - 3 )
2x + 5 = 14,8 + x - 3
2x - x = 14,8 - 3 - 5
x = 6,8
b) 0.25x - ( 4 + 0.5x ) = -2
0.25x - 4 - 0.5x = -2 |*100
25x - 400 -50x = -200
25x = 200 |/25
x = 8
c) 2 ( 3 - x ) - 4 ( x - 5 ) = 2x + 2
6 - 2x - 4x + 20 = 2x + 2
26 - 6x = 2x + 2
26 - 2 = 6x + 2x
24 = 8x |/8
x = 3
d) 1/3 * (-6x + 9) - 4 = -5 (x+1)
-2x + 3 - 4 = -5x -5
-2x -1 = -5x - 5
-2x + 5x = -5 +1
-3x = 4 |/(-3)
x = -4/3
e) 0.2 * (10-5x) = 3 + 2 (x-1)
2 - x = 3 + 2x -2
2 - 3 + 2 = 2x +x
1 = 3x
1/3 = x